Effects of Alkalinity and pH on Survival, Growth, and Enzyme Activities in Juveniles of the Razor Clam, Sinonovacula constricta - Maoxiao, Peng; Bo, Ye; Xiaojun, Liu; Donghong, Niu; Tianyi, Lan; Zhiguo, Dong; Jiale, Li (Frontiers in Physiology, 2018)
In order to clarify the possibility of rearing razor clams (Sinonovacula constricta) in inland saline water (ISW) and to facilitate their breeding under these stressful conditions, we performed semi-static acute and chronic toxicity tests to determine the effects of carbonate alkalinity (CA) and pH on the survival and growth rate, and critical metabolic enzyme activity in juvenile of S. constricta (JSC). (1) Acute toxicity test. As the water CA increased from 1.22 to 45.00 mmol L–1, the survival rate decreased significantly, which was exacerbated by the increase in the pH. When the water CA was set at 2.5 mmol L–1, the 48 h lethal concentration 50% (LC50) for JSCs with respect to pH was 9.86. When the water pH was 9.0, 9.5, and 10.0, the 48 h LC50 values for JSCs with respect to CA were 10.38, 8.79, and 3.11 mmol L–1, respectively. (2) Chronic toxicity test. After 3 months of stress, the JSC survival rate in each group exceeded 85%, but survival was significantly lower in the CA-pHS group than the control group (p < 0.05) in the first month. For the JSCs in various groups, the shell length growth rate (SGR) and weight gain rate (WG) were significantly lower in the CA-pHS group than the other groups (p < 0.05 for SGR; p < 0.001 for WG) in the first month. However, the difference in the growth rate among groups decreased in the next two months. For the JSCs in the CA-pHS group, the oxygen consumption, ammonia-N excretion, Na+/K+-ATPase, aspartate aminotransferase, and superoxide dismutase levels were significantly higher than those in the other groups during the first month, but there were no significant differences between the groups subsequently. The acetylcholinesterase and lysozyme levels did not differ significantly among groups during stress for 3 months. The integrated biomarker response index showed that stressors comprising high pH and CA could be tolerated well by JSCs over long periods of stress. These results indicate that water CA and pH together affect the survival, growth, and physiological activity of JSCs. S. constricta is suitable for culture in ISW.